2015
DOI: 10.1038/srep16304
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Visual Impairment and Eye diseases on Mortality: the Singapore Malay Eye Study (SiMES)

Abstract: We investigated the relationship of visual impairment (VI) and age-related eye diseases with mortality in a prospective, population-based cohort study of 3,280 Malay adults aged 40–80 years between 2004–2006. Participants underwent a full ophthalmic examination and standardized lens and fundus photographic grading. Visual acuity was measured using logMAR chart. VI was defined as presenting (PVA) and best-corrected (BCVA) visual acuity worse than 0.30 logMAR in the better-seeing eye. Participants were linked wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 59 publications
(85 reference statements)
7
62
0
Order By: Relevance
“…Eight studies were conducted in women19 22 23 28 31 33 35 36 and seven in men 22 23 28 31 33 35 36. With regard to the study region, nine studies were conducted in North America,4 16 18–20 35 36 four in Oceania,21 22 29 seven in Asia17 23 25 26 28 30 and nine in Europe 24 27 31–34 37. Follow-up duration ranged from 2 to 13.2 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies were conducted in women19 22 23 28 31 33 35 36 and seven in men 22 23 28 31 33 35 36. With regard to the study region, nine studies were conducted in North America,4 16 18–20 35 36 four in Oceania,21 22 29 seven in Asia17 23 25 26 28 30 and nine in Europe 24 27 31–34 37. Follow-up duration ranged from 2 to 13.2 years.…”
Section: Resultsmentioning
confidence: 99%
“…There were nine studies with a follow-up duration shorter than 5 years,4 21 23 27 28 32 36 six studies with a follow-up duration between 5 and 6 years,16 31 33 34 37 seven studies with a follow-up duration between 6 and 8 years17 22 26 30 35 and seven studies with a follow-up duration longer than 8 years 18–20 24 25 29. About VI assessment, 15 studies were assessed by acuity charts,17 19 21 23–27 29–31 33 34 three studies by the International Statistical Classification of Diseases (ICD) code,4 35 seven studies by self-report16 22 28 32 37 and four by other methods 18 20 36. The baseline characteristics of the studies are shown in online supplementary table S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalent ocular pathologies in non‐Indigenous Australians such as cataract, age‐related macular degeneration, glaucoma and DR have all been independently linked not only to VI but also to increased risk of mortality and, in some cases, they can be predictive of mortality . However, these findings have not been consistently shown, and the exact reason behind these relationships remains elusive . It is suggested that some eye diseases can be biological markers for cellular ageing .…”
Section: Discussionmentioning
confidence: 99%
“…VI is typically classified as visual acuity worse than 6/12 vision in a person's better‐seeing eye and has been shown to be associated with higher mortality even after efforts to control for confounders such as age and sex . Some studies also controlled for additional confounders such as socioeconomic status, hypertension, diabetes, smoking, body mass index and history of CVD, and these remained evident . Causes of VI can vary within populations, ages, gender and educational and ethnic groups.…”
Section: Introductionmentioning
confidence: 99%